1991
DOI: 10.1152/ajprenal.1991.261.6.f998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin on renal cortical and papillary blood flows measured by laser-Doppler flowmetry

Abstract: The effects of angiotensin II (ANG II) or angiotensin III (ANG III) on renal cortical blood flow (CBF) or papillary blood flow (PBF) were investigated in Inactin-anesthetized young rats with the use of laser-Doppler flowmetry. Infusion of equimolar pressor doses of ANG II (300 ng.kg-1.min-1 iv) or ANG III (267 ng.kg-1.min-1) decreased CBF by 31 +/- 2.6% (P less than 0.001) and 20.3 +/- 3.2% (P less than 0.01), respectively but increased PBF by 19 +/- 6.1% (P less than 0.05) and 14.6 +/- 4.4% (P less than 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
57
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 0 publications
10
57
4
Order By: Relevance
“…MBF has been reported to increase, 20 decrease, 21 or remain unchanged 22 during Ang II infusion to the anesthetized rat. More recently, by using laser-Doppler flowmetry techniques enabling the direct and continuous recording of changes in MBF, Mattson et al 6,7 found that the medullary circulation of anesthetized Sprague-Dawley rats was very refractory to Ang II vasoconstrictor actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MBF has been reported to increase, 20 decrease, 21 or remain unchanged 22 during Ang II infusion to the anesthetized rat. More recently, by using laser-Doppler flowmetry techniques enabling the direct and continuous recording of changes in MBF, Mattson et al 6,7 found that the medullary circulation of anesthetized Sprague-Dawley rats was very refractory to Ang II vasoconstrictor actions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Nobes et al 20 reported increases in papillary blood flow when even higher concentrations of Ang II (300 ng ⅐ kg Ϫ1 ⅐ min Ϫ1 ) were infused. The relative insensitivity of the medullary circulation to Ang II may be explained in part by the stimulation of medullary prostaglandin 6 or kinin production, 20 although the long-term effects of these pathways on MBF remain to be explored. The present study, however, demonstrates that Ang II-induced NO production contributes importantly to the long-term ability of the organism to buffer against the hypertensive actions of circulating Ang II.…”
mentioning
confidence: 99%
“…Changes in renal CBF are not always replicated in the medullary or papillary regions because medullary hemodynamics can be regulated independently of renal CBF (Pallone et al 1990, Navar et al 1996, Mattson 2003. Vasoactive agents, including AngII, dopamine, arginine vasopressin, atrial natriuretic peptide, and bradykinin have been demonstrated to induce renal region-specific hemodynamic changes (Takezawa et al 1987, Pallone et al 1990, Nobes et al 1991, Mattson & Cowley 1993, Heyman et al 1995, Badzynska et al 2002, Igbe et al 2012. However, the effect of UII on regional RBF was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Manotham et al (2004) demonstrated a reduced PTC blood flow and interstitial hypoxia before the development of structural damage to renal tissues in an early phase of remnant kidney model rats. Although the precise mechanisms responsible for the pathogenesis of peritubular ischemia are currently unclear, a potential contribution of the renin-angiotensin system has been suggested (Nobes et al, 1991;Lombardi et al, 1999;Omoro et al, 2000;Franco et al, 2001;Norman et al, 2003;Welch et al, 2003aWelch et al, ,b, 2005Manotham et al, 2004). Acute infusion of angiotensin II (AngII) resulted in renal cortical vasoconstriction (Nobes et al, 1991) or hypoxia (Norman et al, 2003).…”
mentioning
confidence: 99%
“…Although the precise mechanisms responsible for the pathogenesis of peritubular ischemia are currently unclear, a potential contribution of the renin-angiotensin system has been suggested (Nobes et al, 1991;Lombardi et al, 1999;Omoro et al, 2000;Franco et al, 2001;Norman et al, 2003;Welch et al, 2003aWelch et al, ,b, 2005Manotham et al, 2004). Acute infusion of angiotensin II (AngII) resulted in renal cortical vasoconstriction (Nobes et al, 1991) or hypoxia (Norman et al, 2003). Likewise, cortical hypoxia was observed in the kidneys of chronically AngII-infused hypertensive rats (Welch et al, 2005) and in the clipped kidney at an early phase of twokidney, one-clip Goldblatt hypertensive rats (Welch et al, 2003b).…”
mentioning
confidence: 99%